Implementasi Metode Talqin Talaqqi Di SD Qurrota A’yun Yogyakarta - Ani Widiyawati; Amanati Khairiyah (Indonesia, 2022)
Memorizing the Al-Qur’an is one of the efforts of Muslims to maintain the purity of the Qur’an and is anoble and comendable deed. One method of memorizing the Qur’an is by using talqin talaqqi method. This methode is carried out by the teacher reading the verses thah will be memorized by the students first and foremost, then the students repeat the reading according to what is exemplified by the teacher until the students really memorize it. This study aims to find out how the implementation process and problematics of the talqin talaqqi method exist in SD Qurrota A’yun Yogyakarta. This research is a field research (field research), the approach in this study is descriptive qualitatie, data collection using interview techniques, obeservation and documentation. The data analysys technique of this research is through four stages, namely : data reduction, data presentation, data validity test and conclusions.The results of this study show : first the implementation of the talqin talaqqi method at SD Qurrota A’yun is with the teacher reading five repetitions of the reading that will be memorized by the students, then the students repeat it repearedly until all students are sure to have memorized it whit a unified test. The two problems in memorizing the ur’an using the talqin talaqqi A’yun method, namely : first, the lack of assistance in memorizing children by parents when at home. The two children who lacked concentration while memorizing the Qur’an. The three children have different memorization abilities. Fourth, the child’s psychological condition is not yet stable.